Media – My ”Best” Teacher Curiosities and assumptions - TALAŞMAN-CHIOREAN, Claudia (2020)
The present book emerged from the desire toidentify some effects that technology brings on thehuman psychic in the level of emotions, cognitionsand behaviors, in specific social, cultural, professionalcontexts.Like any element of novelty, the technologicalexplosion brings, besides the impetuous temptation,feelings of uncertainty, fear, concern about the sideeffects on the human psyche, derived from its intenseuse.In a way, history repeats itself. When the bookwas published for the general public, the humanityhave the same anxiety: ʺWill not be the man adverselyaffected by the excessive consumption of books?ʺ Inthe romantic literature, prototype charactersappeared who suffered from endless readings andintense study. The idea of learning was associatedwith the disease (possibly lung disease or somemental illness).